2021
DOI: 10.3389/fpsyg.2021.702553
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to Birth Surname Retention Upon Marriage: How Do Hostile Sexism and System Justification Predict Support for Marital Surname Change Among Women?

Abstract: Despite the ongoing shift in societal norms and gender-discriminatory practices toward more equality, many heterosexual women worldwide, including in many Western societies, choose to replace their birth surname with the family name of their spouse upon marriage. Previous research has demonstrated that the adherence to sexist ideologies (i.e., a system of discriminatory gender-based beliefs) among women is associated with their greater endorsement of practices and policies that maintain gender inequality. By i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…This conceptualization, however, might pose some limitations for our understanding of whether (a) participants personally received support when they needed it and (b) significant female others recognized the need and importance of challenging gender inequalities. Future research should also account for the disempowering effects of women's adherence to sexist ideologies and system‐justifying beliefs that were shown to impede a wide range of social and political behaviours (e.g., Chayinska et al, 2021; Jost & Kay, 2005; Radke et al, 2018). Future qualitative studies may be helpful in understanding what female support may entail for women that represent different social and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conceptualization, however, might pose some limitations for our understanding of whether (a) participants personally received support when they needed it and (b) significant female others recognized the need and importance of challenging gender inequalities. Future research should also account for the disempowering effects of women's adherence to sexist ideologies and system‐justifying beliefs that were shown to impede a wide range of social and political behaviours (e.g., Chayinska et al, 2021; Jost & Kay, 2005; Radke et al, 2018). Future qualitative studies may be helpful in understanding what female support may entail for women that represent different social and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2021, Turkey was ranked as having the 133rd largest gender gap among 156 countries (Global Gender Gap Report, 2021). While international observers have documented some progress with respect to gender equality in Turkey in recent decades, the country's conservative religious groups and right‐wing populist parties are committed to restoring the gendered status quo by strengthening patriarchal attitudes and traditional gender roles (see Chayinska, Uluğ, Solak, Kanık, & Çuvaş, 2021; Kabasakal‐Arat, 2020).…”
Section: Study 3: Turkeymentioning
confidence: 99%
“…In another study by Kaynak Malatyalı et al (2017), hostile sexism was found to mediate the relationship between social dominance orientation and approval of child marriages. Chayinska et al (2021) also reported that hostile sexist attitudes predicted positive attitudes toward changing women's surnames due to marital union through system justification tendencies. Accordingly, we can claim that hostile sexism predicts violation of women's rights, such as approving the rape perpetrator, approving the girl child marriages, violence against women, and supporting women to take their husbands' surnames, and it is negatively related to support for women's rights.…”
Section: Ambivalent Sexismmentioning
confidence: 95%
“…For example, studies have shown that women sometimes prefer to choose stereotypically female-oriented occupations and training (e.g., Stoet & Geary, 2018) and perceive themselves to be less entitled to stereotypically male-dominated positions (e.g., managers and politicians). Some women also tend to support the claim that it is men's right (a) to earn more than women (Major, 1987, 1994), (b) to engage in more productive work, (c) to do less housework relative to women (Monacelli & Caricati, 2010), and even (d) for women to replace their surnames with their husband's upon marriage (Chayinska et al, 2021). Although there is consensus that people tend to support the prevailing realities in their societies, there is much less agreement on why the disadvantaged sometimes do so, given that it ostensibly undercuts their interests (e.g., the case of women supporting male privilege; for related discussions on the “why” debate see Jost, 2019; Owuamalam et al, 2019a, 2019b; Owuamalam & Spears, 2020; see also Rubin et al, 2023a, 2023b).…”
mentioning
confidence: 94%
“…However, other progressive women who are similarly invested in their gender identity (e.g., feminist women) may challenge those arrangements (e.g., Bashi et al, 2018; Hercus, 1999; Radke et al, 2016). 1 So, while gender socialization could account for some instances of gender system justification (Chayinska et al, 2021; Jost & Kay, 2005), it seems insufficient to fully explain why women who are strongly invested in their gender identity (both traditional and feminist women) do not uniformly support a system of gender inequality. Some do, such as women who subscribe to traditional roles, and some do not, such as feminist women who challenge such roles.…”
mentioning
confidence: 99%